Question
upstudy study bank question image url

The graph of \( g(x)=a\left(\frac{1}{5}\right)^{x}-5 \) passes throughi \( (-2 ;-4) \). 7.1 Show that \( a=\frac{1}{25} \) 7.2 Determine the coordinates of the \( x \) intere \( E^{4} f_{8} \), 7.3 Given: \( h(\tau)=\left(\frac{1}{5}\right)^{x} \) 7.3.1 Determine the cquation of \( x^{-1}(x) \), the inverse of \( h \), in the forks \( y=- \) 7.3.2 Describe the transformation from. g to h .

Ask by Stuart Powers. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a = 1/25 x-intercept of g is at (–3, 0) Inverse of h is h⁻¹(x) = –log₅ x Transformation from g to h: compress vertically by 1/25 and shift down by 5 units

Solution

We are given that   g(x) = a·(1/5)^x – 5 and that the point (–2, –4) lies on the graph of g. We also have a related function   h(x) = (1/5)^x. Below are the steps to solve each part. ───────────────────────────── Step 7.1. Show that a = 1/25 Since (–2, –4) is on the graph of g, we substitute x = –2 and g(–2) = –4 into the equation:   –4 = a·(1/5)^(–2) – 5. Recall that (1/5)^(–2) = 5² = 25. Thus, we have   –4 = a·25 – 5. Now, add 5 to both sides:   –4 + 5 = 25a   1 = 25a. Finally, divide both sides by 25:   a = 1/25. ───────────────────────────── Step 7.2. Determine the coordinates of the x-intercept of g The x-intercept is found by setting g(x) = 0. That is, solve   0 = a·(1/5)^x – 5. We now substitute a = 1/25 into the equation:   0 = (1/25)·(1/5)^x – 5. Add 5 to both sides:   (1/25)·(1/5)^x = 5. Multiply both sides by 25 to isolate (1/5)^x:   (1/5)^x = 125. Recall that 125 = 5³. Also note that (1/5)^x = 5^(–x). Therefore,   5^(–x) = 5³. Since the bases are the same, equate the exponents:   –x = 3 ⟹ x = –3. Thus, the x-intercept is at (–3, 0). ───────────────────────────── Step 7.3. Inverse of h and the transformation from g to h 7.3.1. Find the inverse function h⁻¹ The function is given by   h(x) = (1/5)^x. It is often useful to write this as   h(x) = 5^(–x). To find the inverse, start with   y = 5^(–x). Swap x and y:   x = 5^(–y). Now solve for y by taking the logarithm with base 5 on both sides:   log₅(x) = –y ⟹ y = –log₅(x). Thus, the inverse function is   h⁻¹(x) = –log₅(x). 7.3.2. Describe the transformation from g to h Recall that   g(x) = a·(1/5)^x – 5  with a = 1/25  so that g(x) = (1/25)·(1/5)^x – 5,   h(x) = (1/5)^x. We can express g in terms of h as follows:   g(x) = (1/25)·h(x) – 5. Thus, compared to h, the graph of g is obtained by: 1. Vertically compressing h by a factor of 1/25. 2. Then shifting the resulting graph downward by 5 units. Equivalently, starting with g, if one “undoes” these transformations (that is, first shifting upward by 5 units and then stretching vertically by a factor of 25), one obtains h. ───────────────────────────── Summary of Answers 7.1 a = 1/25. 7.2 The x-intercept of g is at (–3, 0). 7.3.1 The inverse of h is h⁻¹(x) = –log₅ x. 7.3.2 The graph of g is obtained from the graph of h by a vertical compression by a factor of 1/25 followed by a downward shift of 5 units. (Conversely, h can be obtained from g by first shifting upward 5 units and then stretching vertically by a factor of 25.) Any answer equivalent to the above is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find \( a \) in the equation \( g(x) = a\left(\frac{1}{5}\right)^{x} - 5 \) that passes through the point \( (-2, -4) \), substitute \( x = -2 \) and set \( g(-2) = -4 \). This gives: \[ -4 = a\left(\frac{1}{5}\right)^{-2} - 5 \] Solving for \( a \): \[ -4 + 5 = a \cdot 25 \implies 1 = 25a \implies a = \frac{1}{25} \] Now, let’s find the \( x \)-intercept by setting \( g(x) = 0 \): \[ 0 = \frac{1}{25}\left(\frac{1}{5}\right)^{x} - 5 \] Solving gives: \[ \frac{1}{25}\left(\frac{1}{5}\right)^{x} = 5 \implies \left(\frac{1}{5}\right)^{x} = 125 \implies x = -3 \] So, the \( x \)-intercept is \( E( -3; 0) \). For the inverse of \( h(x) = \left(\frac{1}{5}\right)^{x} \), set \( y = \left(\frac{1}{5}\right)^{x} \), then take the logarithm: \[ x = -\log_{5}(y) \implies y = -\log_{5}(x) \] To describe the transformation from \( g \) to \( h \), you can say that \( h(x) \) is derived from \( g(x) \) by first applying an exponential decay function followed by a vertical stretch by \( a \) and a downward shift by \( -5 \). This gives \( g \) a more transformed appearance, moving it down the graph while scaling its outputs based on the factor \( a \).

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy